Investigating the use and associated constraints of urban networks among the Klang Valley Residents, Malaysia - Paneerchelvam, Patheebaa (2020)
This PhD studies the topic of the use and associated constraints urban green network in Malaysian context. Although the use of urban green network has gained considerable attention in the West, only a limited number of studies have addressed this topic in a non-Western context. Moreover, none of the studies in industrialising countries have focused on environmental cues such as the element of concealments (e.g. vegetation or landscape settings which influence the users) and the presence of the disorders (e.g graffiti, trash) in influencing use of urban green network.These studies also did not look into social cues as presence of strangers, drug addicts and the like, nor on the other hand of individuals whose presence promotes sense of safety in public. In addition, not many of the past studies have examined how use of urban green network differs among different socio demographic characterizes. It was therefore seen as timely to study use and associated constraints of urban green network from an Asian perspective by looking into different demographic characteristics and different levels of environmental cues. Hence, a study was conducted at two selected urban green networks in Klang Valley, Kuala Lumpur: Kuala Lumpur South West Bicycle Corridor (KLSWBC) and Shah Alam Bicycle Lane (SABL). The study was conducted to fill the existing void and is composed of three stages of reviews: systematic, quantitative and qualitative. The socio-ecological approach was used as a framework to understand attributes influencing use of urban green networks in Klang Valley. The findings from the systematic review included an analysis of available literature with regards to authorship, journal, geographical distribution of studies, types of urban green networks, landscape stimulus used, applied methods, types of respondents involved and findings of other studies. Most of these studies highlighted that physical attributes were more influential compared to individual and social attributes when related to use of urban green networks in the Klang Valley. On-site surveys involving a total of 620 respondents consisted of residents of Klang Valley, aged 18 years old and above. With regards to the descriptive analysis of findings, most of the respondents agreed or provided neutral responses with respect to the constructs. The findings demonstrated that most physical attributes significantly affected use and considered as major constraints while social attributes did not influence same. Independent T- test and Analysis of Variance (ANOVA) were performed to examine relationships between individual characteristics. The findings disclosed that age and education had significant impact on use and reflected as related constraints. The semi-structured interviews provided more in-depth understanding of use and related constraints of urban green network in Klang Valley. Qualitative findings indicated attributes such as physical safety and conditions, social safety, distance and time of day generally had strong influence on use of urban green network. This study revealed theories and findings from Western studies on urban green network use can be generalized to a Malaysian context, in spite of cultural and other differences. This holds important implication for the understanding of green network use in Malaysia and possibly also other countries.